Modelling of corrosion protection for reinforced concrete structures with surface coatings/Gelžbetoninių konstrukcijų su paviršinėmis dangomis korozinės apsaugos modeliavimas - Kamaitis, Zenonas (Journal of Civil Engineering and Management, 2008)
Corrosion is a serious problem for the durability of reinforced concrete structures. These structures need to be protected from corrosion in a variety of exposure conditions ranging from atmospheric to continuous immersion in water or chemicals. One of the ways to protect reinforced concrete structures from corrosion is to use protective coatings. The surface barriers of non‐degradable materials are able to slow down considerably the rate of deterioration of concrete structures and to overcome most durability problems associated with external attack. Design of durability of concrete structures with protective coatings needs to be established. In this paper a general framework for service life prediction and reliability evaluation of anticorrosion protective system (CPS), which is represented by protective surface barrier, concrete cover, and steel reinforcement itself of reinforced concrete structures, is presented. This approach is based on a reasonable understanding of the main degradation processes of all components ensuring protection ability and durability of concrete structures. The effect of repair of CPS components on extending the service life of a whole protective system is considered. Numerical example for reliability verification of CPS is also given. Santrauka Korozija yra svarbi gelžbetoninių konstrukcijų ilgaamžiškumo problema. Gelžbetonines konstrukcijas būtina apsaugoti nuo korozijos įvairiomis sąlygomis, pradedant nuo atmosferos iki nuolatinio mirkymo vandenyje ar chemikaluose. Vienas iš apsaugos būdų yra polimerinės apsauginės dangos. Atsparus paviršinis barjeras gali labai sulėtinti gelžbetonio irimą ir išspręsti daugelį problemų, susijusių su išorine aplinka. Reikia sukurti gelžbetoninių konstrukcijų su apsauginėmis dangomis projektavimo metodiką. Straipsnyje nagrinėjama antikorozinės apsauginės sistemos, susidedančios iš paviršiaus apsauginio barjero, apsauginio betoninio sluoksnio ir pačios plieninės armatūros, patikimumas ir spėjamas gyvavimo laikotarpis. Šis modelis remiasi apsauginio barjero, betonio sluoksnio ir armatūros irimo procesų samprata. Skaitinis pavyzdys rodo antikorozinės apsauginės sistemos patikimumo patikrą. First Published Online: 14 Oct 2010 Reikšminiai žodžiai: gelžbetonis, korozija, antikorozinė apsauga, patikimumas, laikas iki suirties.